Interlayer film, laminate, and laminated glass

CN123022648APending Publication Date: 2026-10-30SEKISUI CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202580024485.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-28
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

根据本发明,其课题在于提供一种含有离聚物树脂的中间膜,其能够抑制由光和热导致的经时黄变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The interlayer film of the present application contains an ionomer resin, an ultraviolet absorber, a phenol-based antioxidant, and an N-C type hindered amine light stabilizer. According to the present application, an interlayer film capable of suppressing yellowing over time caused by light and heat can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an interlayer used in laminated glass, a laminate having an interlayer, and laminated glass. Background Technology

[0002] Laminated glass, even when broken by external impact, produces fewer shards, making it safe. Therefore, it is widely used in windows for various vehicles such as automobiles, railway vehicles, aircraft, and ships, as well as in buildings. As is well known, laminated glass is typically made by sandwiching an interlayer of thermoplastic resin or similar material between two panes of glass, thus creating a unified product. In architectural applications, laminated glass is used not only for windows but also for glass floors and curtain walls. In these applications, it is sometimes produced in larger sizes, and it is also used as structural glass windows.

[0003] In the interlayer of laminated glass, ionomer resins have sometimes been used in the past. Among the ionomer resins used in the interlayer of laminated glass, resins formed by crosslinking at least a portion of the carboxyl groups of the side chains of ethylene-unsaturated carboxylic acid copolymers such as ethylene-(meth)acrylic acid copolymers between molecular chains are known (for example, see Patent Documents 1 to 4).

[0004] Existing technical documents Patent documents Patent Document 1: International Publication No. 2022 / 270545 Patent Document 2: International Publication No. 2022 / 065146 Patent Document 3: Japanese Patent Application Publication No. 2014-58409 Patent Document 4: International Publication No. 2019 / 054363 Summary of the Invention The problem that the invention aims to solve However, laminated glass, for example, when used in buildings, requires the suppression of yellowing over time caused by light and heat.

[0005] When the above-mentioned ionomer resin is used in an intermediate film, although it exhibits excellent strength and transparency, the ionomer resin itself does not have the ability to absorb ultraviolet light, so an ultraviolet absorber needs to be added. However, according to the research of the inventors, when an ultraviolet absorber is added to the ionomer resin, the ends of the intermediate film yellow over time due to heat (end yellowing).

[0006] To address this issue, attempts were made to combine ultraviolet absorbers and antioxidants, but light irradiation tests using xenon as a light source confirmed that the yellowing over time was caused by light.

[0007] Therefore, the objective of this invention is to provide an intermediate film containing an ionomer resin that can suppress yellowing over time caused by light and heat.

[0008] Solution for solving the problem The inventors conducted in-depth research and found that the above-mentioned problems could be solved by using an intermediate film containing an ionomer resin, an ultraviolet absorber, a phenolic antioxidant, and an N-C type hindered amine light stabilizer, thereby completing the following invention. That is, the present invention provides the following [1] to

[23] .

[0009] [1] An intermediate membrane comprising an ionomer resin, an ultraviolet absorber, a phenolic antioxidant, and an N-C type hindered amine light stabilizer.

[0010] [2] According to the intermediate membrane described in [1] above, the phenolic antioxidant has the following structure, which has a phenolic group having a tert-butyl group at at least one ortho position.

[0011] [3] According to the intermediate film described in [1] or [2] above, wherein the N-C type hindered amine light stabilizer has the structure of formula (1).

[0012]

[0013] (In formula (1), 1 and 2 are bonding bonds, the 1 is the bond that bonds to a carbon atom. [4] The intermediate membrane according to any one of [1] to [3] above, wherein the content of the phenolic antioxidant is 0.05 parts by mass or more and 0.50 parts by mass or less relative to 100 parts by mass of the ionomer resin.

[0014] [5] The intermediate film according to any one of [1] to [4] above, wherein the content of the N-C type hindered amine light stabilizer is 0.01 parts by mass or more and 0.50 parts by mass or less relative to 100 parts by mass of the ionomer resin.

[0015] [6] The intermediate membrane according to any one of [1] to [5] above, wherein the content of antioxidant other than the phenolic antioxidant is 0.30 parts by mass or less relative to 100 parts by mass of the ionomer resin.

[0016] [7] The intermediate film according to any one of [1] to [6] above, wherein, relative to 100 parts by weight of the ionomer resin, the content of the hindered amine light stabilizer other than the N-C type hindered amine light stabilizer is 0.30 parts by weight or less.

[0017] [8] The intermediate film according to any one of [1] to [7] above, wherein the additive with the highest melting point among the additives contained in the intermediate film has a melting point of less than 180°C.

[0018] [9] The intermediate membrane according to any one of [1] to [8] above, wherein the ultraviolet absorber is a compound having a benzotriazole structure.

[0019]

[10] The intermediate membrane according to any one of [1] to [9] above contains a silane coupling agent.

[0020]

[11] The intermediate membrane according to any one of [1] to

[10] above, wherein the ionomer resin comprises a structural unit (A) derived from (meth)acrylic acid, a structural unit (B) derived from (meth)acrylic acid neutralizer and a structural unit (C) derived from ethylene.

[0021]

[12] As described in

[11] above, the intermediate membrane, wherein, based on the total amount of structural units constituting the ionomer resin, the total content of the structural units (A) and (B) is 10% by mass or more and 25% by mass or less.

[0022]

[13] According to the intermediate membrane described in

[11] or

[12] above, wherein, based on the total amount of structural units constituting the ionomer resin, the content of the structural unit (B) is 4% by mass or more and 17.5% by mass or less.

[0023]

[14] The intermediate membrane according to any one of

[11] to

[13] above, wherein the structural unit (B) in the ionomer resin comprises sodium, zinc or magnesium.

[0024]

[15] The interlayer film according to any one of [1] to

[14] above, wherein the haze value of the laminated glass made of two pieces of transparent glass with a thickness of 2.0 mm and the interlayer film is less than 2%.

[0025]

[16] A laminate comprising an intermediate film as described in any one of [1] to

[15] above and a pair of substrates, wherein the intermediate film is disposed between the pair of substrates.

[0026]

[17] According to the laminate described in

[16] above, wherein the substrate is a pair of substrates selected from the group consisting of organic material substrates and inorganic material substrates respectively.

[0027]

[18] According to the laminate described in

[16] or

[17] above, wherein at least one of the pair of substrates is the organic material substrate described above, and the organic material substrate is at least one selected from the group consisting of polarizing film, polyethylene terephthalate film, polycarbonate plate and (meth)acrylic plate.

[0028]

[19] A laminated glass comprising any one of the laminates described in any one of

[16] to

[18] .

[0029]

[20] A display comprising any one of the laminates described in any one of

[16] to

[18] above.

[0030]

[21] A building comprising any one of the above

[16] to

[18] .

[0031]

[22] A resin composition comprising an ionomer resin, an ultraviolet absorber, a phenolic antioxidant, and an N-C type hindered amine light stabilizer.

[0032]

[23] A masterbatch comprising an ionomer resin, an ultraviolet absorber, a phenolic antioxidant, and an N-C type hindered amine light stabilizer.

[0033] Invention Effects According to the present invention, the objective is to provide an intermediate film containing an ionomer resin that can suppress yellowing over time caused by light and heat. Detailed Implementation

[0034] The present invention will now be described in detail with reference to embodiments.

[0035] [Intermediate membrane] The intermediate film of the present invention comprises an ionomer resin, an ultraviolet absorber, a phenolic antioxidant, and an N-C type hindered amine light stabilizer.

[0036] The intermediate film of the present invention is an intermediate film containing an ionomer resin, which can suppress yellowing over time caused by light and heat by using ultraviolet absorbers, phenolic antioxidants and N-C type hindered amine light stabilizers.

[0037] The components contained in the intermediate membrane of the present invention will be described in detail below.

[0038] <Ionomer Resins> The intermediate film of this invention contains an ionomer resin. By containing an ionomer resin, the mechanical strength and transparency of the intermediate film are improved.

[0039] Ionomer resins include ionomer resins of ethylene-unsaturated carboxylic acid copolymers. A typical ionomer resin is a resin formed by neutralizing an ethylene-unsaturated carboxylic acid copolymer with metal ions.

[0040] Examples of unsaturated carboxylic acids include: acrylic acid, methacrylic acid, 2-ethylacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, maleic anhydride, fumaric anhydride, itaconic anhydride, monomethyl maleate, and monoethyl maleate. In ionomer resins, one or more unsaturated carboxylic acids may be used alone or in combination. Acrylic acid and methacrylic acid are preferred. Therefore, ionomer resins of ethylene-(meth)acrylic acid copolymers are preferred.

[0041] In addition, the metal ions that can be used include lithium, potassium, sodium, silver, copper, calcium, magnesium, titanium, zinc, aluminum, barium, beryllium, strontium, tin, lead, iron, cobalt, nickel, cadmium, and mercury. Among these, sodium, magnesium, and zinc are preferred, magnesium or zinc are more preferred, and magnesium is particularly preferred. A single metal ion can be used, or two or more can be used in combination. When magnesium and zinc, especially magnesium, are used as metal ions, a suitable cross-linking structure is formed, which easily increases the glass transition temperature of the intermediate film and improves its mechanical strength.

[0042] It should be noted that (meth)acrylic acid refers to at least one of methacrylic acid or acrylic acid, and the same applies to similar terms below.

[0043] In the case of ionomer resins that are ethylene-unsaturated carboxylic acid copolymers, they typically contain structural units (A) derived from unsaturated carboxylic acids, structural units (B) derived from unsaturated carboxylic acid neutralization, and structural units (C) derived from ethylene. In the case of ionomer resins that are ethylene-(meth)acrylic acid copolymers, they typically contain structural units (A) derived from (meth)acrylic acid (hereinafter also referred to as structural unit (A)), structural units (B) derived from (meth)acrylic acid neutralization (hereinafter also referred to as structural unit (B)), and structural units (C) derived from ethylene. Ionomer resins containing these structural units (A), (B), and (C) readily exhibit excellent mechanical strength and transparency.

[0044] The monomer constituting structural unit (A) is not particularly limited as long as it is an unsaturated carboxylic acid, but is preferably at least one of acrylic acid and methacrylic acid. Methacrylic acid is more preferred from the viewpoint of mechanical strength and adhesion. It should be noted that structural unit (A) is a structural unit that has not been neutralized by metal ions.

[0045] Structural unit (B) is a neutralized product of structural units derived from the aforementioned unsaturated carboxylic acids, preferably a structural unit derived from at least one of acrylic acid and methacrylic acid, more preferably a structural unit derived from a neutralized methacrylic acid. Structural unit (B) is a structural unit formed by replacing the hydrogen ion of the carboxyl group in the unsaturated carboxylic acid with a metal ion. That is, the unsaturated carboxylic acid neutralized product in structural unit (B) is a metal salt of the unsaturated carboxylic acid. The metal ion in the metal salt, as described above, is preferably sodium, zinc, or magnesium, more preferably at least one of magnesium and zinc, and particularly preferably magnesium.

[0046] Therefore, structural unit (B) preferably contains sodium, zinc or magnesium, more preferably contains at least one of magnesium and zinc, and particularly preferably contains magnesium.

[0047] In the ionomer resin, based on the total amount of structural units constituting the ionomer resin, the combined content of structural units (A) and (B) is preferably 10% by mass or more and 25% by mass or less. When the combined content of structural units (A) and (B) is 10% by mass or more, the intermediate film exhibits good transparency, heat resistance, mechanical strength, etc. Furthermore, when it is 25% by mass or less, it exhibits good flexibility, processability, adhesion, etc. The combined content of structural units (A) and (B) is more preferably 12% by mass or more and 23% by mass or less, and even more preferably 15% by mass or more and 20% by mass or less.

[0048] In ionomer resins, based on the total amount of structural units constituting the ionomer resin, the content of structural unit (B) is preferably 4% by mass or more and 17.5% by mass or less. When the content of structural unit (B) is 4% by mass or more, the degree of crosslinking of the ionomer resin increases, making it easier to improve mechanical strength. Furthermore, when the content of structural unit (B) is 4% by mass or more, transparency, heat resistance, and other properties are also easily improved. In addition, by keeping the content of structural unit (B) at 17.5% by mass or less, the flexibility, adhesion, mechanical strength, and processability of the interlayer film are easily improved.

[0049] The content of structural unit (B) in the ionomer resin is more preferably 6% by mass or more and 17% by mass or less, more preferably 7% by mass or more and 16% by mass or less, and even more preferably 10% by mass or more and 14% by mass or less.

[0050] The content of structural unit (B) in the ionomer resin is preferably 6% by mass or more, more preferably 7% by mass or more, even more preferably 9% by mass or more, even more preferably 10% by mass or more, and preferably 17% by mass or less, more preferably 16% by mass or less, even more preferably 14% by mass or less, even more preferably 13% by mass or less, and even more preferably 12.5% ​​by mass or less.

[0051] From the viewpoint of easily improving the impact resistance of the ionomer resin, based on the total amount of structural units constituting the ionomer resin, the content of ethylene-derived structural units (C) is preferably 70% by mass or more, more preferably 75% by mass or more, and even more preferably 80% by mass or more. Furthermore, from the viewpoint of transparency, mechanical strength, and processability, the content of ethylene-derived structural units (C) is preferably 90% by mass or less, more preferably 89% by mass or less, even more preferably 88% by mass or less, and even more preferably 85% by mass or less.

[0052] In the ionomer resin, the content of structural unit (A) is not particularly limited, but based on the total amount of structural units constituting the ionomer resin, it is preferably 3% by mass or more and 15% by mass or less, more preferably 4% by mass or more and 10% by mass or less, further preferably 5% by mass or more and 9% by mass or less, and even more preferably 4% by mass or more and 8% by mass or less.

[0053] Ionomer resins can be resins formed by neutralizing copolymers of ethylene and (methyl)unsaturated carboxylic acids with metal ions, or resins formed by neutralizing copolymers of ethylene and unsaturated carboxylic acids with metal ions with monomers other than ethylene and unsaturated carboxylic acids.

[0054] Therefore, as a preferred embodiment, the ionomer resin may contain structural units other than structural units (A), (B) and (C) (hereinafter also referred to as "other structural units").

[0055] Other structural units include structural units (D) derived from alkyl methacrylates. By having structural units (D), the glass transition temperature (Tg) of the ionomer resin can be adjusted, for example. Examples of alkyl methacrylates include methyl methacrylate, ethyl methacrylate, isobutyl methacrylate, n-butyl methacrylate, and 2-ethylhexyl methacrylate, which have approximately 1 to 10 carbon atoms.

[0056] From the viewpoint of not lowering the glass transition temperature of the interlayer to a level necessary above, the content of structural unit (D) derived from (meth)acrylate is preferably 15% by mass or less, more preferably 8% by mass or less, further preferably 4.5% by mass or less, and even more preferably 2% by mass or less. Furthermore, from the viewpoint of not lowering the glass transition temperature and improving mechanical strength at high temperatures, the lower the content of structural unit (D), the better; it can contain 0% by mass or more, and the ionomer resin preferably does not contain structural unit (D).

[0057] Furthermore, while isobutyl methacrylate is generally suitable as an alkyl methacrylate in ionomer resins, in this invention, the ionomer resin preferably does not contain structural units derived from isobutyl methacrylate, or if it does, it is in small amounts. Therefore, the content of structural units derived from isobutyl methacrylate is preferably 15% by mass or less, more preferably 8% by mass or less, further preferably 4.5% by mass or less, and even more preferably 2% by mass or less. Additionally, the content of structural units derived from isobutyl methacrylate can be 0% by mass or more, and the ionomer resin preferably does not contain structural units derived from isobutyl methacrylate.

[0058] In addition, ionomer resins may contain structural units other than structural units (A), (B), (C), and (D) as other structural units, such as structural units derived from vinyl esters such as vinyl acetate and vinyl propionate.

[0059] In this invention, the degree of neutralization of the ionomer resin is, for example, 30% or more, and from the viewpoint of improving mechanical strength, preferably more than 40%, more preferably 42% or more, further preferably 45% or more, and even more preferably 50% or more. The mechanical strength of the ionomer resin can be easily improved by increasing its degree of neutralization.

[0060] Furthermore, in this invention, from the viewpoint of improving mechanical strength, it is preferable to contain at least one of magnesium and zinc (especially magnesium) in the structural unit (B), and to improve the degree of neutralization.

[0061] Furthermore, the degree of neutralization of the ionomer resin is not particularly limited, but from the viewpoint of improving the softness, adhesion, mechanical strength, and processability of the intermediate film, it is preferably 95% or less, more preferably 90% or less, further preferably 80% or less, and even more preferably 75% or less.

[0062] It should be noted that the neutralization degree of ionomer resin refers to the percentage (%) of all carboxyl groups in the ionomer resin that are neutralized by metal ions.

[0063] The degree of neutralization of the aforementioned ionomer resin can be determined by IR (infrared spectroscopy) measurement before and after hydrochloric acid treatment. The specific measurement method is as described in the examples below.

[0064] Furthermore, the content of each structural unit in the aforementioned ionomer resin can be analyzed by mass spectrometry and... 1 The H-NMR (hydrogen nuclear magnetic resonance) measurement is calculated from the integrated intensity ratio and neutralization degree of the hydrogen peaks originating from each monomer.

[0065] When the interlayer film is set to 100% by mass, the content of ionomer resin in the interlayer film is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and even more preferably 88% by mass or more. By setting the content of ionomer resin to the above-mentioned lower limit value, the resulting laminated glass can have good rigidity, interlayer adhesion, etc.

[0066] Furthermore, when the intermediate membrane is set to 100% by mass, from the viewpoint of containing a certain amount or more of additives, the content of ionomer resin in the intermediate membrane can be, for example, 99.99% by mass or less, or 99.9% by mass or less.

[0067] Furthermore, when the ionomer resin in the intermediate membrane contains other resin components, the content of the ionomer resin in the intermediate membrane is preferably below a certain amount, for example, it can be below 98.4% by mass, below 97.4% by mass, or below 96.4% by mass.

[0068] There is no particular limitation on the manufacturing method of ionomer resins. They can be manufactured by known methods. For example, ethylene-unsaturated carboxylic acid copolymers can be obtained by free radical copolymerization of the monomer components under high temperature and high pressure, and then the copolymers can be reacted with metal compounds to obtain the resins.

[0069] <Other Resin Components> In addition to the ionomer resin described above, the intermediate film of the present invention may also contain other resin components. By containing other resin components, the intermediate film of the present invention readily exhibits good extrusion and other formability properties. As other resin components, resins compatible with the ionomer resin are preferred. From the viewpoint of compatibility with the aforementioned ionomer resin, ethylene-unsaturated carboxylic acid copolymers are preferred as other resin components. Here, the unsaturated carboxylic acid used in the ethylene-unsaturated carboxylic acid copolymer is as described above, with (meth)acrylic acid being preferred, and methacrylic acid being more preferred.

[0070] Furthermore, from the viewpoints of compatibility and extrudability, it is preferable to use copolymers of the same type as those used in the aforementioned ionomer resin as other resin components. To obtain the aforementioned ionomer resin, it is even more preferable to use the resin before neutralization with metal ions. Therefore, when the aforementioned ionomer resin is an ionomer resin of ethylene-(meth)acrylic acid copolymer, the other resin components are preferably ethylene-(meth)acrylic acid copolymers. Furthermore, when the aforementioned ionomer resin is an ionomer resin of ethylene-methacrylic acid copolymer, the other resin components are preferably ethylene-methacrylic acid copolymers.

[0071] When using other resin components, if the entire intermediate film is set to 100% by mass, the content of other resin components is preferably 1.5% by mass or more and 25% by mass or less. By setting the content of other resin components to 1.5% by mass or more, the viscosity of the aforementioned ionomer resin is easily reduced, resulting in good extrudability. Furthermore, by setting it to 25% by mass or less, even with the presence of other resin components, a decrease in mechanical strength can be prevented. When the entire intermediate film is set to 100% by mass, the content of other resin components is more preferably 2.5% by mass or more and 18% by mass or less, and even more preferably 3.5% by mass or more and 11% by mass or less.

[0072] <Phenolic antioxidants> The intermediate membrane of this invention contains a phenolic antioxidant.

[0073] Phenolic antioxidants refer to antioxidants that have a phenolic group in their chemical structure. Among phenolic antioxidants, from the viewpoint that they can easily suppress light- and heat-induced yellowing of the intermediate film by being used in conjunction with ultraviolet absorbers and N-C type hindered amine light stabilizers, phenolic antioxidants with a structure having a phenolic group having a tert-butyl group at at least one ortho position are preferred. Furthermore, phenolic antioxidants with a structure having a phenolic group having a tert-butyl group at two ortho positions are more preferred.

[0074] A phenolic antioxidant having a structure having a phenolic group having a tert-butyl group at at least one ortho position is, in other words, a phenolic antioxidant having the structure shown in the following formula (2).

[0075]

[0076] In equation (2) above, there is a tert-butyl group at at least one position of a and b.

[0077] Furthermore, in the above formula (2), it is preferable to have tert-butyl groups at positions a and b.

[0078] The number of structures represented by formula (2) in the phenolic antioxidant is preferably one or more, more preferably two or more, more preferably three or more, and usually six or less.

[0079] Examples of commercially available phenolic antioxidants having a structure with a phenol group having a tert-butyl group at at least one ortho position include "Irganox 1010", "Irganox 1076", and "Irganox 245" manufactured by BASF, "RIANOX 1010" manufactured by Rianlon, and "ADK STAB AO-20", "ADK STAB AO-30", "ADK STAB AO-40", "ADK STAB AO-50", "ADK STAB AO-60", "ADK STAB AO-80" manufactured by ADEKA.

[0080] The phenolic antioxidant may be used alone, or two or more thereof may be used in combination.

[0081] The content of the phenolic antioxidant relative to 100 parts by mass of the ionomer resin is not particularly limited, and is preferably 0.05 parts by mass or more and 0.5 parts by mass or less, more preferably 0.1 parts by mass or more and 0.4 parts by mass or less.

[0082] When the content of the phenolic antioxidant is not less than these lower limits, it is easy to suppress time-dependent yellowing of the interlayer film caused by light and heat. When the content of the phenolic antioxidant is not more than these upper limits, it is easy to obtain an effect corresponding to the added amount, use in an amount more than necessary can be suppressed, and in addition, the composition for forming the interlayer film can be easily kneaded.

[0083] The interlayer film of the present invention may contain an antioxidant other than the above-mentioned phenolic antioxidant, but from the viewpoint of suppressing time-dependent yellowing of the interlayer film caused by light and heat, the content thereof is preferably reduced. Relative to 100 parts by mass of the ionomer resin, the content of the antioxidant other than the phenolic antioxidant is preferably 0.3 parts by mass or less, more preferably 0.1 parts by mass or less, and still more preferably 0 parts by mass.

[0084] <N-C type hindered amine light stabilizer> The interlayer film of the present invention contains an N-C type hindered amine light stabilizer.

[0085] Hindered amine light stabilizers are known as additives also referred to as HALS, and are compounds having a hindered amine structure. Here, the hindered amine structure usually has a 2,2,6,6-tetramethylpiperidine skeleton.

[0086] The N-C type hindered amine light stabilizer has a structure in which the nitrogen atom in the hindered amine structure is bonded to a carbon atom other than the carbon atoms constituting the cyclic structure of the hindered amine. More specifically, the N-C type hindered amine light stabilizer is a compound having a structure of the following formula (1).

[0087]

[0088] (In formula (1), 1 and 2 are bonding bonds, the 1 is the bond that bonds to a carbon atom. The N-C type hindered amine light stabilizer in this invention may have only one structure as shown in formula (1) above, or it may have two or more structures. The number of structures shown in formula (1) is preferably one or two.

[0089] In equation (1) There is no particular limitation on the type of bond, as long as it is a bond bonded to a carbon atom. For example, it can be a bond bonded to an organic group R1 having 1 to 10 carbon atoms. The organic group R1 may contain oxygen atoms, nitrogen atoms, etc. From the viewpoint of suppressing yellowing over time caused by light and heat, the organic group R1 is preferably an alkyl group having 1 to 10 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and even more preferably a methyl group.

[0090] In equation (1) 2 is a bond that is bonded to any group R2. For example, R2 can be a hydroxyl group, an organic group with 1 to 20 carbon atoms, etc. The organic group with 1 to 20 carbon atoms can be an organic group with a valence of 1 to 3. For example, if R2 is an organic group with a valence of 2 or more, the N-C type hindered amine light stabilizer can have a plurality of structures shown in formula (1).

[0091] The number of structures represented by formula (1) in N-C type hindered amine light stabilizers can be 1, preferably 2 or more, and more preferably 2.

[0092] N-C type hindered amine light stabilizers can be commercially available products, such as those manufactured by BASF, including "Tinuvin 765", "Tinuvin PA144", "Tinuvin 292", and "Tinuvin 622". Among these, Tinuvin 765 is preferred.

[0093] N-C type hindered amine light stabilizers can be used alone or in combination with two or more.

[0094] The content of N-C type hindered amine light stabilizer relative to 100 parts by weight of ionomer resin is not particularly limited, but is preferably 0.01 parts by weight or more and 0.5 parts by weight or less, more preferably 0.03 parts by weight or more and 0.4 parts by weight or less, and even more preferably 0.07 parts by weight or more and 0.3 parts by weight or less.

[0095] When the content of N-C type hindered amine light stabilizer is above these lower limits, it is easy to suppress light and heat-induced yellowing of the intermediate film over time. When the content of N-C type hindered amine light stabilizer is below these upper limits, it is easy to obtain an effect corresponding to the amount added, suppressing the use of more than the necessary amount, and it is also easy to mix the composition used to form the intermediate film.

[0096] The interlayer of the present invention may contain hindered amine light stabilizers other than the aforementioned N-C type hindered amine light stabilizers. From the viewpoint of suppressing light- and heat-induced yellowing of the interlayer, it is preferable to reduce their content. The content of hindered amine light stabilizers other than N-C type hindered amine light stabilizers is preferably 0.3 parts by weight or less, more preferably 0.1 parts by weight or less, and even more preferably 0 parts by weight, relative to 100 parts by weight of the ionomer resin.

[0097] <UV absorber> The intermediate membrane of this invention contains an ultraviolet absorber.

[0098] Examples of previously known ultraviolet absorbers include compounds with malonic acid ester structures, compounds with oxaloylaniline structures, compounds with benzotriazole structures, compounds with benzophenone structures, compounds with triazine structures, compounds with benzoic acid ester structures, and compounds with hindered amine structures. Ultraviolet absorbers can be used alone or in combination with two or more.

[0099] Among these UV absorbers, compounds having a benzotriazole structure are preferred from the viewpoint that they can easily suppress the light- and heat-induced yellowing of the intermediate film by using them in combination with phenolic antioxidants and N-C type hindered amine light stabilizers.

[0100] From the viewpoint that it is easier to suppress the staining of the intermediate film, the compound shown in the following formula (3) is preferred as a compound having a benzotriazole structure.

[0101]

[0102] (In the above formula, R1 is an organic group with 4 or more carbon atoms, and R2 to R8 are each an organic group with 1 to 20 carbon atoms.) In the above formula (3), R1 is an organic group with 4 or more carbon atoms. As a result, the coloring of the intermediate film is easily suppressed. The reason for this is still uncertain, but it is speculated that R1 is a group located at the ortho position of the hydroxyl group in formula (3). Because it is an organic group with 4 or more carbon atoms, it is easy to suppress the coordination of the ultraviolet absorber with the metal in the ionomer resin. As a result, the coloring of the intermediate film can be suppressed.

[0103] From the viewpoint of further suppressing the coloration of the intermediate film, R1 is preferably an organic group with 4 or more but less than 20 carbon atoms, and more preferably an organic group with 4 or more but less than 10 carbon atoms. R1 may contain oxygen atoms, nitrogen atoms, sulfur atoms, etc., and is preferably a hydrocarbon group.

[0104] That is, R1 is preferably a hydrocarbon group with 4 or more carbon atoms, more preferably a hydrocarbon group with 4 or more and 20 or less carbon atoms, and even more preferably a hydrocarbon group with 4 or more and 10 or less carbon atoms.

[0105] Furthermore, R1 preferably possesses either or both of a quaternary carbon atom and an aromatic ring. It is speculated that by having such a structure, it is easier to suppress the coordination of the ultraviolet absorber with the metal present in the ionomer resin, and as a result, the coloration of the intermediate film can be further suppressed.

[0106] R1 is particularly preferably a group represented by the following formula (a) or formula (b).

[0107]

[0108] Equations (a) and (b) The bond is the bond that bonds to the aromatic ring shown in equation (3).

[0109] In the above formula (3), R2 to R8 are each an organic group with 1 to 20 hydrogen atoms or carbon atoms. As such an organic group, it may contain oxygen atoms, nitrogen atoms, sulfur atoms, etc., or it may be a hydrocarbon group.

[0110] In the above formula (3), R2, R4, R5, R6, R7 and R8 are each preferably hydrogen atoms, alkyl, aryl, alkoxy, aryloxy, acyloxy, alkylamino, aniline, acylamino, alkylsulfonylamino, arylsulfonylamino, alkylthio or arylthio, wherein hydrogen atoms are more preferred.

[0111] In formula (3) above, R3 is a hydrogen atom or an organic group having 1 to 20 carbon atoms. This organic group may include oxygen atoms, nitrogen atoms, sulfur atoms, or a hydrocarbon group. From the viewpoint of further suppressing the staining of the intermediate film, R3 is preferably an organic group having 1 to 10 carbon atoms, more preferably a hydrocarbon group having 1 to 10 carbon atoms, or an organic group having 1 to 10 carbon atoms with an ester structure. Furthermore, the aforementioned hydrocarbon group having 1 to 10 carbon atoms preferably possesses either a quaternary carbon atom or an aromatic ring, or both.

[0112] R3 is particularly preferred to be a group represented by formula (c), formula (d) or formula (e) below.

[0113]

[0114] Equations (c), (d), and (e) The bond is the bond that bonds to the aromatic ring shown in equation (3).

[0115] From the viewpoint of inhibiting the coloration of the intermediate film of the present invention, among the compounds having a benzotriazole structure in formula (3), any of the compounds in formulas (4) to (6) below are preferred, and compounds in formula (4) or (5) are more preferred.

[0116]

[0117] As ultraviolet absorbers with a benzotriazole structure, commercially available products can be used, such as: BASF's "Tinuvin 640", "Tinuvin 326", "Tinuvin 234", "Tinuvin 328", and Rianlon's RIASORB UV-326, UV-327, UV-328, UV-928, UV-234, etc.

[0118] The content of the UV absorber relative to 100 parts by weight of the ionomer resin is not particularly limited, but is preferably 0.05 parts by weight or more and 0.5 parts by weight or less, more preferably 0.1 parts by weight or more and 0.4 parts by weight or less. When the content of the UV absorber is above these lower limits, it is easy to suppress the yellowing of the interfilm caused by light and heat over time. When the content of the UV absorber is below these upper limits, it is easy to obtain an effect corresponding to the amount added, and it is possible to suppress the use of more than the necessary amount. In addition, it is easy to mix the composition used to form the interfilm.

[0119] <Silane Coupling Agent> The interlayer may contain additives other than the aforementioned ultraviolet absorbers, phenolic antioxidants, and N-C type hindered amine light stabilizers. Preferably, the interlayer contains, for example, a silane coupling agent as the additive. By containing a silane coupling agent, the interlayer readily improves its adhesion to substrates, glass, and the like. Examples of silane coupling agents include those having functional groups such as vinyl or (meth)acryloyl groups containing polymeric carbon-carbon double bonds, amino or epoxy groups, and hydrolyzable groups such as alkoxy groups.

[0120] Examples of silane coupling agents with polymerizable carbon-carbon double bonds include: vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropylmethyldiethoxysilane, 3-acryloxypropyltriethoxysilane, etc.

[0121] Examples of amino-containing silane coupling agents include: N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and hydrochloride salts of N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane.

[0122] Examples of epoxy-containing silane coupling agents include: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxypropoxypropylmethyldimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, and 3-epoxypropoxypropyltriethoxysilane.

[0123] The intermediate membrane may contain only one silane coupling agent or two or more.

[0124] From the viewpoint of improving adhesion to glass and substrates, silane coupling agents are preferably silane coupling agents having an amino group, wherein N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane is preferred.

[0125] From the viewpoint of improving adhesion to glass and substrate, when the interlayer film is set to 100% by mass, the content of silane coupling agent in the interlayer film is preferably 0.001% by mass or more and 5% by mass or less, more preferably 0.005% by mass or more and 2% by mass or less, further preferably 0.01% by mass or more and 1% by mass or less, and even more preferably 0.05% by mass or more and 0.5% by mass or less.

[0126] <Other Additives> The intermediate membrane of the present invention may contain other additives besides the ultraviolet absorber, phenolic antioxidant, N-C type hindered amine light stabilizer and silane coupling agent mentioned above.

[0127] Other additives include, for example: plasticizers, light stabilizers, antistatic agents, surfactants, colorants, foaming agents, lubricants, crystallization nucleating agents, crystallization promoters, crystallization retarders, catalyst deactivators, heat radiation absorbers, heat radiation reflectors, heat dissipation agents, inorganic fillers, organic fillers, impact resistance modifiers, slip agents, crosslinking agents, crosslinking aids, tackifiers, processing aids, release agents, hydrolysis inhibitors, anti-blocking agents, antifogging agents, flame retardants, flame retardant additives, light diffusing agents, antibacterial agents, antifungal agents, dispersants, etc.

[0128] <Melting point of additives> The intermediate membrane of the present invention contains the aforementioned ultraviolet absorber, phenolic antioxidant, and N-C type hindered amine light stabilizer as additives. Furthermore, the intermediate membrane of the present invention may, as needed, contain silane coupling agents and other additives mentioned above as additives.

[0129] From the viewpoint of facilitating the mixing of the resin composition used to form the intermediate film, the melting point of the additive with the highest melting point among the additives contained in the intermediate film is preferably less than 200°C, more preferably less than 180°C, and even more preferably less than 180°C.

[0130] Here, the melting point of the additive is set as the endothermic peak temperature of the melting curve determined using a DSC (differential scanning calorimeter). It should be noted that the DSC is measured from room temperature (25°C) at a heating rate of 10°C / min.

[0131] <MFR of the intermediate membrane> From the viewpoint of increasing the extrusion amount of the resin composition used to form the intermediate film, or facilitating molding and processing, the melt flow rate (MFR) of the intermediate film of the present invention is, for example, 0.01 g / 10 min or more and 150 g / 10 min or less, preferably 0.01 g / 10 min or more and 50 g / 10 min or less, more preferably 0.1 g / 10 min or more and 30 g / 10 min or less, further preferably 0.1 g / 10 min or more and 10 g / 10 min or less, and even more preferably 1 g / 10 min or more and 5 g / 10 min or less.

[0132] It should be noted that the MFR of the intermediate membrane was determined according to JIS K7210-1 (2014) at 190℃ and a load of 2.16 kg.

[0133] <Haze> The interlayer of the present invention, particularly when used in buildings, preferably possesses high transparency. From this perspective, the haze value of laminated glass made from two sheets of 2.0 mm thick transparent glass and the interlayer of the present invention is preferably 2% or less, more preferably 1% or less, and even more preferably 0.5% or less. It should be noted that the haze value can be measured according to JIS K7105:1981.

[0134] <Thickness> The thickness of the interlayer is not particularly limited, but is preferably 0.2 mm or more and 4 mm or less. By setting the thickness of the interlayer to 0.2 mm or more, the mechanical strength, adhesion, and penetration resistance of the interlayer when it is made into laminated glass are all good. In addition, by setting it to 4 mm or less, the transparency of the interlayer is also easily ensured.

[0135] The thickness of the interlayer is more preferably 0.4 mm or more, and even more preferably 0.6 mm or more. Furthermore, it is more preferably 2.5 mm or less, even more preferably 1.6 mm or less, and even more preferably 1.0 mm or less.

[0136] <width> The width of the interlayer film in this invention is preferably 1 m or more. By making the width of the interlayer film 1 m or more, it can be suitable for use in large-sized laminated glass, laminated glass for building structures, etc. The width of the interlayer film is more preferably 2 m or more. In addition, the interlayer film is not particularly limited, but from the viewpoint of maximizing productivity, it is preferably 5 m or less, and more preferably 4 m or less.

[0137] Furthermore, the intermediate film of the present invention is preferably an extruded product obtained by extrusion molding as described later. By using an extruded product, even if the intermediate film is a large size with a width of 1m or more as described above, it is easy to mass-produce in industry.

[0138] <Resin Composition> In this invention, a resin composition for forming the aforementioned intermediate film can also be provided. This resin composition has the same composition as the intermediate film described above. That is, the resin composition includes an ionomer resin, a UV absorber, a phenolic antioxidant, and an N-C type hindered amine light stabilizer. Furthermore, additives such as silane coupling agents may be included in the resin composition as needed.

[0139] The contents of the ionomer resin, ultraviolet absorber, phenolic antioxidant, N-C type hindered amine light stabilizer, and silane coupling agent, etc., in the resin composition are as described in the intermediate film section above.

[0140] <Masterbatch> In this invention, a masterbatch comprising the aforementioned ionomer resin, ultraviolet absorber, phenolic antioxidant, and N-C type hindered amine light stabilizer can also be provided. For example, this masterbatch can be mixed with the ionomer resin to obtain the aforementioned resin composition, and an intermediate film can be made using this resin composition. When using the masterbatch, the ultraviolet absorber, phenolic antioxidant, and N-C type hindered amine light stabilizer can be easily mixed with the ionomer resin.

[0141] This masterbatch can be made by mixing ionomer resin, ultraviolet absorber, phenolic antioxidant, and N-C type hindered amine light stabilizer. The form of the masterbatch is not particularly limited; typically, it can be made into granules or other particulate forms.

[0142] The content of each component in the masterbatch is not particularly limited, but the following are preferred.

[0143] The content of ultraviolet absorber in the masterbatch is preferably 0.01 parts by mass and 10 parts by mass or less, more preferably 0.1 parts by mass and 5 parts by mass or less, relative to 100 parts by mass of ionomer resin.

[0144] The content of phenolic antioxidant in the masterbatch is preferably 0.05 parts by mass and 10 parts by mass or less, more preferably 0.1 parts by mass and 8 parts by mass or less, relative to 100 parts by mass of ionomer resin.

[0145] Relative to 100 parts by weight of ionomer resin, the content of N-C type hindered amine light stabilizer in the masterbatch is preferably 0.01 parts by weight or more and 10 parts by weight or less, more preferably 0.1 parts by weight or more and 5 parts by weight or less.

[0146] <Composition of the intermediate membrane> The intermediate film of the present invention is preferably composed of a monolayer film formed by a single layer. The layer constituting the monolayer film can be formed from the above-described resin composition. That is, the layer constituting the monolayer film can be formed from a resin composition containing an ionomer resin, an ultraviolet absorber, a phenolic antioxidant, and an N-C type hindered amine light stabilizer, and the monolayer film can be formed from this resin composition.

[0147] Furthermore, the intermediate film of the present invention can be a multilayer film with two or more layers. The multilayer film only needs to have the overall composition as described in the intermediate film above, and the resin composition constituting each layer can have the composition described in the intermediate film above. That is, each layer, as described in the intermediate film above, can be formed from a resin composition containing an ionomer resin, an ultraviolet absorber, a phenolic antioxidant, and an N-C type hindered amine light stabilizer. In the multilayer film, the compositions of each layer can be different from each other or the same.

[0148] <Method for manufacturing intermediate membrane> Regarding the intermediate film, it is preferable to obtain a resin composition for forming the intermediate film and then mold the intermediate film from the resin composition. Regarding the intermediate film, the components constituting the intermediate film, such as ionomer resin, ultraviolet absorber, phenolic antioxidant, N-C type hindered amine light stabilizer, and additives as needed, can be mixed to obtain a resin composition. The obtained resin composition is then appropriately heated to melt, and formed into a film shape by extrusion molding, compression molding, roll forming, etc., to obtain the intermediate film. The method for mixing the components to obtain the resin composition is not particularly limited, but a method using an extruder for mixing is preferred. It should be noted that, as mentioned above, a resin composition obtained by mixing a masterbatch and an ionomer resin can be used.

[0149] Furthermore, when the intermediate film is formed from multiple layers, a resin composition for forming each layer can be prepared. The obtained resin composition is appropriately heated and melted, and then formed into a film shape by extrusion molding, compression molding, roll forming, etc. The layers are then stacked to obtain the intermediate film. When the intermediate film is formed from multiple layers, extrusion molding can be carried out by co-extrusion.

[0150] Of the above, the intermediate film is preferably formed by extrusion molding. By using extrusion molding, wide intermediate films can be manufactured efficiently.

[0151] <Layered Body> In this invention, a laminate having the aforementioned interlayer film can be provided. Specifically, a laminate having an interlayer film and a pair of substrates, with the interlayer film disposed between the pair of substrates, can be provided. In the laminate, the pair of substrates can be bonded together with the interlayer film in between. Furthermore, in the laminate, the interlayer film disposed between the pair of substrates can be a single sheet, or multiple interlayer films can be disposed between the pair of substrates. By disposing multiple interlayer films between the pair of substrates, even in applications such as laminated glass for buildings where it is necessary to increase the thickness of the interlayer film between a pair of glass components, a solution of a generally acceptable thickness can be achieved using an interlayer film. It should be noted that multiple interlayer films can be integrally formed between the substrates, and a pair of substrates can be bonded together via the integrally formed multiple interlayer films.

[0152] The total thickness of the interlayer film between the substrates in the laminate is not particularly limited, but is, for example, 0.2 mm or more and 6 mm or less, preferably 0.4 mm or more and 4.5 mm or less, and more preferably 0.6 mm or more and 3.6 mm or less.

[0153] Other layers may be disposed between the interlayer film and the substrate, but it is preferable to dispose of them without other layers and to arrange them in direct contact with the substrate. Furthermore, when using multiple interlayer films, other layers may be disposed between them, but it is preferable to dispose of them without other layers and to arrange the interlayer films in direct contact with each other.

[0154] The aforementioned substrate is a pair of substrates selected from the group consisting of organic material substrates and inorganic material substrates, respectively. Two substrates in a pair can be organic material substrates, two substrates can be inorganic material substrates, or one substrate can be an organic material substrate and the other substrate can be an inorganic material substrate.

[0155] Organic resin substrates include organic resin boards and resin films. Organic resin boards are also known as plexiglass boards. There are no specific limitations on organic resin boards; examples include: polycarbonate boards, polymethyl methacrylate boards, (meth)acrylic boards, acrylonitrile-styrene copolymer boards, acrylonitrile-butadiene-styrene copolymer boards, polyethylene terephthalate boards, polyester boards, fluorinated resin boards, polyvinyl chloride boards, chlorinated polyvinyl chloride boards, polypropylene boards, polystyrene boards, polysulfone boards, epoxy resin boards, phenolic resin boards, unsaturated polyester resin boards, polyimide resin boards, and various other plexiglass boards. Organic resin boards can undergo appropriate surface treatments.

[0156] The thickness of the organic resin board is not particularly limited, but it is preferably 0.1 mm or more, more preferably 0.4 mm or more, and preferably 5.0 mm or less, more preferably 3.0 mm or less.

[0157] Resin films are not particularly limited, but examples include: (meth)acrylic resin films, polycarbonate films, polyethylene terephthalate (PET) films, polyethylene naphthalate (PEN) films, and other polyester resin films; polyethylene films, polypropylene films, and other polyolefin resin films; cyclic polyolefin (COP) films; triacetyl cellulose (TAC) films; polyethersulfone (PES) resin films; and polyimide resin films. Furthermore, resin films can be polarizing films. Functional layers such as hard coatings formed from (meth)acrylic resins can be appropriately applied to the surface of the resin film, and electrodes, sensors, etc., can also be mounted on it.

[0158] The thickness of the resin film is not particularly limited, but it is preferably 30 μm or more, more preferably 50 μm or more, and preferably 500 μm or less, more preferably 450 μm or less.

[0159] Of the above, the organic material substrate is preferably at least one selected from the group consisting of a polarizing film, a polyethylene terephthalate film, a polycarbonate sheet, and a (meth)acrylic sheet.

[0160] Inorganic glass sheets can be used as inorganic material substrates. There are no particular limitations on inorganic glass sheets; examples include float glass, tempered glass, tinted glass, polished glass, patterned glass, mesh glass, wire-reinforced glass, ultraviolet-absorbing glass, infrared-reflecting glass, infrared-absorbing glass, and various other glass sheets. Inorganic glass can undergo surface treatments. The thickness of inorganic glass is not particularly limited, but is preferably 0.1 mm or more, more preferably 1.0 mm or more, and preferably 5.0 mm or less, more preferably 3.0 mm or less.

[0161] Using the laminate of the present invention, laminated glass having the laminate can be manufactured.

[0162] Laminated glass comprises a pair of substrates and an interlayer disposed between the pair of substrates. As the substrates, glass components selected from the aforementioned inorganic glass sheets and plexiglass sheets can be used.

[0163] When the laminate is laminated glass, for example, one or more interlayer films are sandwiched between two glass components. Air remaining between the two glass components and the interlayer film is degassed by pressing rollers or by placing the film in a rubber bag for depressurization. Then, pre-bonding is performed at approximately 70–110°C to obtain a laminated intermediate. Next, the laminated intermediate is placed in an autoclave or pressed under pressure at approximately 120–150°C and 1–1.5 MPa to perform the final bonding. This yields laminated glass. It should be noted that when multiple interlayer films are placed between a pair of glass components, the multiple interlayer films can be integrated through either pre-bonding or final bonding.

[0164] The interlayer film, laminate, and laminated glass of the present invention can be used in various fields, including electronic devices such as displays, vehicles such as automobiles, railway vehicles, aircraft, and ships, and various buildings such as buildings, apartments, detached houses, halls, and stadiums. Among these, it is preferred for use in vehicles and buildings, where the interlayer film, as well as the laminate and laminated glass containing it, are less prone to yellowing over time due to light and heat, and therefore are more preferably used in buildings.

[0165] Laminated glass is preferred for use in vehicles and buildings. Furthermore, in vehicle applications, it can be used as window glass, for example, in automobiles as any of the front, rear, or side windows.

[0166] In buildings, laminated glass can be used for window glass, glass floors, curtain walls, etc. When used in buildings, laminated glass can be made in larger sizes, and it can also be used as structural glass windows.

[0167] [Example] The invention is further illustrated in detail by way of examples, but the invention is not limited by these examples.

[0168] It should be noted that the determination and evaluation of various physical properties are carried out as follows.

[0169] [Thickness of the interlayer] The thickness of the intermediate film was measured using an Olympus DSX500 microscope by averaging 10 points.

[0170] [Content and neutralization degree of each structural unit] The mass percentage of each structural unit of the ionomer resin was determined after the following hydrochloric acid treatment. 1It is determined by H-NMR and IR measurements.

[0171] [Hydrochloric acid treatment] For 100 mg of sample cryogenically pulverized using a JFC-2000 (manufactured by Japan Analysis Industries Co., Ltd.), add 500 μL of ethanol and 1 mL of hydrochloric acid, and stir at 60 °C for 48 hours. Then, wash with ultrapure water approximately three times to remove hydrochloric acid, and dry by heating.

[0172] [Neutralization degree] The degree of neutralization was determined by IR measurements of the samples before and after hydrochloric acid treatment. The IR values ​​before and after hydrochloric acid treatment were taken as the reference values. -1 Based on the peak height of the methylene group, from 1700 cm⁻¹ -1 The peak height of the carboxylic acid was calculated using the following formula. It should be noted that in the following formula, the denominator represents the peak height of the sample treated with hydrochloric acid at 1700 cm⁻¹. -1 Peak height / 1460cm -1 The peak height, represented by the molecule, is 1700 cm⁻¹ in the sample before hydrochloric acid treatment. -1 Peak height / 1460cm -1 The peak height.

[0173]

[0174] [ 1 [H-NMR determination] The hydrochloric acid-treated sample was dissolved in a solvent (tetrachloroethane: dimethyl sulfoxide = 5:2) to prepare the assay solution at a concentration of approximately 1–3% by mass. The assay solution was then subjected to… 1 ¹H-NMR determination (apparatus: AVANCE 400 (PRODIGY), spectrometer: AVANCE III HD). Measurement conditions were 8 cumulative measurements at 120°C. In the analysis, the integral value of the H from the methyl group derived from methacrylic acid was used as a baseline, set to 3.00. The content of structural units (A) and (B) as a total mass percentage and the content of structural unit (C) derived from ethylene were calculated from the integral intensity ratio of the H peaks derived from methylene groups appearing at 1.15–1.62 ppm. Furthermore, the content of structural units (A) and (B) was calculated using the aforementioned neutralization degree.

[0175] <MFR of the intermediate membrane> For the intermediate membranes of each embodiment and comparative example, the MFR was measured at 190°C and under a load of 2.16 kg according to JIS K7210-1 (2014).

[0176] <Haze of the intermediate membrane> The interlayer film (5cm long × 5cm wide) of each embodiment and comparative example was clamped between two pieces of transparent glass (5cm long × 5cm wide × 2.0mm thick) according to JIS R3202 (2011) to obtain a laminate. The laminate was placed in a rubber bag and degassed under a vacuum of 2.6 kPa for 20 minutes. While degassed, it was transferred to an oven and further vacuum-pressed at 90°C for 30 minutes to temporarily bond the laminate. In an autoclave, the temporarily bonded laminate was pressed for 20 minutes at 135°C and 1.2 MPa to obtain a laminated glass formed from a glass plate / interlayer film / glass plate.

[0177] For the laminated glass manufactured as described above, the haze value was measured using the HAZE METER "HM-150N" manufactured by Murakami Color Co., Ltd., in accordance with JIS K6714.

[0178] Evaluation of Yellowness Changes Based on Heat Resistance Tests Laminated glass was manufactured using the interlayer films of the various embodiments and comparative examples, in the same manner as described in the determination of haze of the interlayer film above. The yellow index value (YI value) of this laminated glass was measured at 23°C. This value was used as the initial YI value.

[0179] Then, the laminated glass was placed in an oven at 100°C for 3000 hours. After being removed from the oven, and with the surface temperature of the laminated glass reaching 23°C, the yellow index value (YI value) was measured. This value was taken as the YI value after the heat resistance test. ΔYI was calculated using the following formula and evaluated according to the following criteria. It should be noted that the YI value was measured using a spectrophotometer (Hitachi High-Tech Co., Ltd. "U-4100") according to JIS K7105:1981, based on the transmission method, to determine the obtained YI value (yellowness, yellow index) of the laminated glass.

[0180] ΔYI = YI value after heat resistance test - initial YI value (Evaluation criteria based on changes in yellowness from heat resistance tests) A: The ΔYI in the heat resistance test is below 2. B: ΔYI exceeds 2 in the heat resistance test. In addition, the laminated glass after the above heat resistance test is visually evaluated to determine whether there is yellowing at the ends.

[0181] (Evaluation of end yellowing after heat resistance test) A: Yellowing without end B: Yellowing at the ends <Evaluation of Yellowness Changes Based on Light Irradiation Experiments> Following the same procedure as described in the determination of haze of the interlayer film above, laminated glass was fabricated using the interlayer films of the various examples and comparative examples. For this laminated glass, the yellow index value (YI value) was measured at 23°C. This value was used as the initial YI value.

[0182] Then, the laminated glass was irradiated with a xenon (Xe) light source for 3,000 hours.

[0183] The light irradiation test was conducted using a Suga SX-75 testing machine. The laminated glass (before the light irradiation test) was fixed to the sample holder with one end exposed. Xenon light (60 W / m² irradiance, measured at 300–400 nm wavelength) was applied to one side of the fixed laminated glass surface for 3000 hours at a black panel temperature of 63°C and a bath humidity of 50% RH. (Inner filter: quartz, outer filter: #275) After irradiation, the glass was allowed to cool until the surface temperature reached 23°C, at which point the yellow index (YI value) was measured. This value was used as the YI value after irradiation. ΔYI was calculated using the following formula and evaluated according to the following criteria.

[0184] ΔYI = YI value after light irradiation - Initial YI value (Evaluation criteria based on changes in yellowness from light irradiation tests) A: ΔYI in the light irradiation test is below 1.5. B: ΔYI exceeds 1.5 in the light irradiation test. <Overall Evaluation: Judgment> A: The results of the evaluation based on the yellowing change from the heat resistance test, the evaluation of the end yellowing after the heat resistance test, and the evaluation based on the yellowing change from the light irradiation test are all A. B: Case where at least one of the following evaluation criteria is B: evaluation of yellowing changes based on heat resistance test, evaluation of end yellowing after heat resistance test, or evaluation of yellowing changes based on light irradiation test. <Regarding the components used in the examples and comparative examples> (Resin) • Ionomer Resin: An ionomer resin prepared by neutralizing an ethylene-methacrylic acid copolymer with magnesium ions, containing Mg as the metal species, 66% neutralization degree, 6.7% by mass of structural unit (A), 13.0% by mass of structural unit (B), and 80.3% by mass of structural unit (C). It is referred to as "Ionomer Resin 1" in Table 1.

[0185] • Polyvinyl alcohol acetal resin: average degree of polymerization 3300, hydroxyl content 30.8 mol%, degree of acetylation 0.8 mol%, degree of acetalization 68.4 mol%, represented as "PVB1" in Table 1.

[0186] (Antioxidants) • Phenolic antioxidants: BASF's "IRGANOX 1010" is an antioxidant containing four phenolic groups with tert-butyl groups at two ortho positions. Melting point 110–125℃ • Phosphorus-based antioxidant: "ADK STAB 2112" manufactured by ADEKA, powder, melting point 180-190℃ • Phosphorus-based antioxidant: "ADK STAB 3010" manufactured by ADEKA, which is liquid at room temperature (25°C). (UV absorber) • Ultraviolet absorber: Ultraviolet absorber with benzotriazole structure, BASF's "Tinuvin 640", melting point 109-113℃, shown as "UV-640" in Table 1.

[0187] • Ultraviolet absorber: Ultraviolet absorber with benzotriazole structure, manufactured by BASF as "Tinuvin 326", melting point 137~141℃, indicated as "T-326" in Table 1.

[0188] (Light stabilizer) • N-C type hindered amine light stabilizer: BASF's "Tinuvin 765" is a hindered amine light stabilizer with two structures represented by formula (1). It is shown as "HS765" in Table 1. It is liquid at room temperature (25°C).

[0189] (Silane coupling agent) Silane coupling agent: "KBM-602", manufactured by Shin-Etsu Chemical Industry Co., Ltd., N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane. It is liquid at room temperature (25°C).

[0190] [Example 1] 100 parts by weight of ionomer resin 1, 0.3 parts by weight of antioxidant (IRGANOX 1010), 0.2 parts by weight of ultraviolet absorber (UV-640), 0.1 parts by weight of N-C type hindered amine light stabilizer (HS765), and 0.15 parts by weight of silane coupling agent (KBM-602) were fed into an extruder, mixed at 170°C, and extruded to obtain an intermediate film with a thickness of 0.76 mm and a width of 1 m. The aforementioned evaluations were performed using this intermediate film.

[0191] [Examples 2-4, Comparative Examples 1-12] As shown in Table 1, the types and amounts of each component were varied, and the intermediate membrane was obtained in the same manner as in Example 1. The aforementioned evaluations were then performed using this intermediate membrane.

[0192] [Table 1]

[0193] The intermediate film shown in each embodiment is an intermediate film containing ionomer resin, ultraviolet absorber, phenolic antioxidant and N-C type hindered amine light stabilizer. Laminated glass made using this intermediate film can suppress yellowing over time caused by light and heat.

[0194] In contrast, Comparative Examples 1-11 are examples of intermediate films containing ionomer resins but without the use of at least one of ultraviolet absorbers, phenolic antioxidants, and N-C type hindered amine light stabilizers, which cannot suppress yellowing over time caused by light and heat.

[0195] Furthermore, Comparative Example 12 is an example in which ultraviolet absorbers, phenolic antioxidants, and N-C type hindered amine light stabilizers are used together, but polyvinyl acetal resin is used instead of ionomer resin as the resin. In Comparative Example 12, end yellowing occurred during the heat resistance test.

[0196] In summary, from the viewpoint of suppressing yellowing over time caused by light and heat in intermediate films containing ionomer resins, the use of ultraviolet absorbers, phenolic antioxidants, and N-C type hindered amine light stabilizers is effective.

Claims

1. An intermediate membrane, wherein, It contains ionomer resin, ultraviolet absorber, phenolic antioxidant and N-C type hindered amine light stabilizer.

2. The intermediate membrane according to claim 1, wherein, The phenolic antioxidant has the following structure, which includes a phenolic group having a tert-butyl group at at least one ortho position.

3. The intermediate membrane according to claim 1 or 2, wherein, The N-C type hindered amine light stabilizer has the structure of formula (1). In equation (1), 1 and 2 are bonding bonds, the 1 represents a bond bonded to a carbon atom.

4. The intermediate membrane according to claim 1 or 2, wherein, The content of the phenolic antioxidant is 0.05 parts by weight or more and 0.5 parts by weight or less, relative to 100 parts by weight of the ionomer resin.

5. The intermediate membrane according to claim 1 or 2, wherein, The content of the N-C type hindered amine light stabilizer is 0.01 parts by mass and less than 0.5 parts by mass relative to 100 parts by mass of the ionomer resin.

6. The intermediate membrane according to claim 1 or 2, wherein, The content of antioxidants other than phenolic antioxidants is less than 0.3 parts by mass relative to 100 parts by mass of the ionomer resin.

7. The intermediate membrane according to claim 1 or 2, wherein, Relative to 100 parts by weight of the ionomer resin, the content of hindered amine light stabilizers other than the N-C type hindered amine light stabilizer is 0.3 parts by weight or less.

8. The intermediate membrane according to claim 1 or 2, wherein, The additives in the intermediate film have the highest melting point, which is less than 180°C.

9. The intermediate membrane according to claim 1 or 2, wherein, The ultraviolet absorber is a compound having a benzotriazole structure.

10. The intermediate membrane according to claim 1 or 2, wherein, The intermediate membrane contains a silane coupling agent.

11. The intermediate membrane according to claim 1 or 2, wherein, The ionomer resin comprises structural units (A) derived from (meth)acrylic acid, structural units (B) derived from (meth)acrylic acid neutralizer, and structural units (C) derived from ethylene.

12. The intermediate membrane according to claim 11, wherein, In the ionomer resin, based on the total amount of structural units constituting the ionomer resin, the total content of structural units (A) and (B) is 10% by mass or more and 25% by mass or less.

13. The intermediate membrane according to claim 11, wherein, In the ionomer resin, based on the total amount of structural units constituting the ionomer resin, the content of the structural unit (B) is 4% by mass or more and 17.5% by mass or less.

14. The intermediate membrane according to claim 11, wherein, The structural unit (B) in the ionomer resin contains sodium, zinc, or magnesium.

15. The intermediate membrane according to claim 1 or 2, wherein, The haze value of the laminated glass, made of two pieces of transparent glass with a thickness of 2.0 mm and the interlayer film, is less than 2%.

16. A laminate comprising an intermediate film as described in claim 1 or 2 and a pair of substrates, the intermediate film being disposed between the pair of substrates.

17. A laminated glass having the laminate as described in claim 16.

Citation Information

Patent Citations

  • Intermediate film for laminated glass and laminated glass

    JP2014058409A

  • Resin composition for laminated glass interlayer film or solar cell encapsulant, laminated glass interlayer film, laminated glass, solar cell encapsulant, and solar cell module

    WO2019054363A1

  • Resin composition, method of manufacturing resin composition, solar cell encapsulant, method of manufacturing solar cell encapsulant, solar cell module, resin sheet for laminated glass interlayer film and laminated glass

    WO2022065146A1

  • Ionomer resin composition, resin sheet, and laminated glass

    WO2022270545A1